Joint association of sleep duration and depression with new-onset hearing loss: a national cohort study - Wang, Fang; Xiong, Yu-Jun; Shao, Da-Ming; Lv, Tian; Chen, Shiqin; Zhu, Qian-Yuan (Frontiers in Nutrition, 2025)
BackgroundHearing loss, a global health burden, is closely associated with depression and sleep disorders. However, the combined effects of sleep duration and depression on hearing loss risk remain unclear.MethodsData from the China Health and Retirement Longitudinal Study (CHARLS) were analyzed, including 6,374 adults aged 45 and older. Cox proportional hazards models assessed the relationship between depression, sleep duration, and hearing loss. Mediation analysis explored the potential mediating roles of CESD-10 score and sleep duration on new-onset hearing loss. Subgroup analyses by age, sex, and BMI were also conducted.ResultsOver a 7-year follow-up, 1,422 participants developed hearing loss. Both short sleep duration and high CESD-10 scores were independently associated with increased risk of hearing loss. Participants with long sleep duration but depression had a hazards ratio (HR) of 1.59 (95% CI: 1.35, 1.87) for hearing loss. Mediation analysis showed that sleep duration mediated 10.1% of the association between CESD-10 score and hearing loss, while CESD-10 score mediated 70.8% of the relationship between sleep duration and hearing loss.ConclusionThis study highlights the significant and interconnected roles of sleep duration and depression in the development of hearing loss. Interventions addressing both sleep and depression may offer more effective strategies for preventing and managing hearing loss.